Solidification of tannery sludge with various binders - Feride Ulu (MANAS: Journal of Engineering)
The treatment of tannery sludge is an issue that has received considerable attention due to the potential of tannery sludge to cause severe environmental damage. In this study, the solidification process of the waste sludge of the Istanbul Tannery Organize Industry Wastewater Treatment Plant was investigated for safe disposal. The solidification technique was applied using various binders and their different mixtures, such as active carbon, gypsum (CaSO4/2H2O), fly ash, lime (CaO), zeolite, and different cement-sand mixtures on the laboratory scale. The essential parameters such as TOC, fluoride (F- mg/l), chloride (Cl- mg/l), sulfate (SO4= mg/l), chromium (VI) (Cr6+ mg/l), and ammonium (NH4+ mg/l) were determined after solidification process at certain conditions. The analysis results of treated sludge samples were compared to the criteria for storage in the landfills in the Hazardous Waste Control Regulation (HWCR) as well as cost-calculation was done at optimum conditions. After the addition of 10% wt. CaSO4 in the solidification study, the eluate concentration of TOC, Cl- and SO4= was below the limit values. When tannery sludge was solidified using CaO, the necessary criteria could not be obtained. On the other hand, with the addition of 33% CaO and 5% AC mixture TOC and AOX were observed below the limit values. The solidification was occured with mörtel + portland cement and 5% activated carbon additives and the desired limit values in HWCR were succussed for all parameters. Besides, with the addition of 30% zeolite, all parameters declined below the limit values.